The X-ray coronae of the two brightest galaxies in the Coma cluster. Issue 1 (5th February 2014) - Sanders, J. S.; Fabian, A. C.; Sun, M.; Churazov, E.; Simionescu, A.; Walker, S. A.; Werner, N.
ABSTRACT: We use deep Chandra X-ray Observatory observations to examine the coronae of the two brightest cluster galaxies in the Coma cluster of galaxies, NGC 4874 and NGC 4889. We find that NGC 4889 hosts a central depression in X-ray surface brightness consistent with a cavity or pair of cavities of radius 0.6 kpc. If the central cavity is associated with an active galactic nuclei (AGN) outburst and contains relativistic material, its enthalpy should be around 5 × 10 55 erg. The implied heating power of this cavity would be around an order of magnitude larger than the energy lost by X-ray emission. It would be the smallest and youngest known cavity in a brightest cluster galaxy and the lack of over pressuring implies heating is still gentle. In contrast, NGC 4874 does not show any evidence for cavities, although it hosts a well-known wide-angle-tail radio source which is visible outside the region occupied by the X-ray corona. These two galaxies show that AGN feedback can behave in varied ways in the same cluster environment.